Deciphering Obesity-Related Gene Clusters Unearths SOCS3 Immune Infiltrates and 5mC/m6A Modifiers in Ossification of Ligamentum Flavum Pathogenesis - Zhang, Baoliang; Yuan, Lei; Chen, Guanghui; Chen, Xi; Yang, Xiaoxi; Fan, Tianqi; Sun, Chuiguo; Fan, Dongwei; Chen, Zhongqiang (Frontiers in Endocrinology, 2022)
Background: Ossification of ligamentum flavum (OLF) is an insidious and debilitating heterotopic ossifying disease with etiological heterogeneity and undefined pathogenesis. Obese individuals predispose to OLF, whereas the underlying connections between obesity phenotype and OLF pathomechanism are not fully understood. Therefore, this study aims to explore distinct obesity-related genes and their functional signatures in OLF. Methods: The transcriptome sequencing data related to OLF were downloaded from the GSE106253 in the Gene Expression Omnibus (GEO) database. The obesity-related differentially expressed genes (ORDEGs) in OLF were screened, and functional and pathway enrichment analysis were applied for these genes. Furthermore, protein-protein interactions (PPI), module analysis, transcription factor enrichment analysis (TFEA) and experiment validation were used to identify hub ORDEGs. The immune infiltration landscape in OLF was depicted, and correlation analysis between core gene SOCS3 and OLF-related infiltrating immune cells (OIICs) as well as 5mC/m6A modifiers in OLF was constructed. Results: Ninety-nine ORDEGs were preliminarily identified, and functional annotations showed these genes were mainly involved in metabolism, inflammation and immune-related biological functions and pathways. Integrative bioinformatic algorithms determined a crucial gene cluster associated with inflammatory/immune responses, such as TNF signaling pathway, JAK-STAT signaling pathway and regulation of interferon-gamma-mediated signaling. Eight hub ORDEGs were validated, including 6 downregulated genes (SOCS3, PPARG, ICAM-1, CCL2, MYC and NT5E) and 2 upregulated genes (PTGS2 and VEGFA). Furthermore, 14 differential OIICs were identified by ssGSEA and xCell, and SOCS3 was overlapped to be the core gene, which was associated with multiple immune infiltrates (dendritic cells, macrophage and T cells, etc.) and six m6A modifiers as well as four 5mC regulators in OLF. Reduced SOCS3 and FTO expression and upregulated DNMT1 level in OLF were validated by Western blotting. Conclusion: This study deciphered immune/inflammatory signatures of obesity-related gene clusters for the first time, and defined SOCS3 as one core gene. The crosstalk between 5mC/m6A methylation may be a key mediator of SOCS3 expression and immune infiltration. These findings will provide more insights into molecular mechanisms and therapeutic targets of obesity-related OLF.